Cyrus the Great as a “King of the City of Anshan” - Zournatzi, Antigoni (Tekmeria, 2019)
In the famous inscription of the Cylinder of Cyrus the Great composed after the fall of Babylon in 539 BC, the founder of the Persian empire is referred to as “king of the city of Anshan” and is made to indicate that this title was equally borne by his ancestors, Cambyses, Cyrus and Teispes. Reference to the venerable –but nonetheless Elamite and to all appearances no longer politically important at the time– city of Anshan in Cyrus’ royal fami- ly titulary has triggered much scholarly discussion. It is currently thought that the references to Cyrus’ dynastic association with Anshan might acknowledge some sense of an Elamite affinity on the part of Cyrus’ royal line. The present study argues that the title “king of the city of Anshan” of Cyrus and his forebears was meant to accommodate traditional perceptions of “legitimate kingship” within a native Mesopotamian/Elamite environment and cannot be used as evidence for an Elamite affiliation of Cyrus’ dynastic line.